Processing–Microstructure–Property Relationships in a Laser‐Deposited Fe‐Co‐V Alloy. Issue 4 (2nd December 2021) - Firdosy, Samad; Ury, Nicholas; Borgonia, John Paul; McEnerney, Bryan; Conversano, Ryan; Hofer, Richard; Hermann, Adam; Ucar, Huseyin; Ravi, Vilupanur A.; Dillon, R. Peter
Abstract : The microstructure and magnetic performance of Fe49Co2V (Hiperco50) manufactured via laser‐directed energy deposition are determined. In the as‐printed form, the material displays a fine, equiaxed microstructure and magnetically "hard" behavior. With a customized post‐process annealing treatment, significant grain growth occurs, resulting in soft magnetic performance comparable to traditionally manufactured materials. An inverse correlation between laser power and post‐anneal grain size is observed, with lower laser powers resulting in samples with larger grain sizes after annealing. Samples printed with lower laser powers also display improvements in soft magnetic performance. This is consistent with the expected relationships between grain size, magnetic permeability, and magnetic coercivity, i.e., as grain size increases, magnetic permeability increases and magnetic coercivity decreases. A prototype magnetic shield for a Hall‐effect thruster is successfully printed. The magnetic performance of the printed and annealed shield is comparable to one that is traditionally manufactured. Abstract : Fabrication of soft magnetic alloy FeCo‐2V is demonstrated using blown powder directed energy deposition (DED). Soft magnetic performance comparable to state‐of‐the‐art wrought FeCo‐2V is achieved through thoughtful design of printing parameters and post‐process thermal treatments. A correlation between laser printing parameters, post‐thermal processing, grain size, and magnetic properties is observed, indicating the possibility of spatial control of magnetic behavior.